Plant Nitrate Reductases Regulate Nitric Oxide Production and Nitrogen-Fixing Metabolism During the Medicago truncatula–Sinorhizobium meliloti Symbiosis - Berger, Antoine; Boscari, Alexandre; Horta Araújo, Natasha; Maucourt, Mickaël; Hanchi, Mohamed; Bernillon, Stéphane; Rolin, Dominique; Puppo, Alain; Brouquisse, Renaud (Frontiers in Plant Science, 2020)
Nitrate reductase (NR) is the first enzyme of the nitrogen reduction pathway in plants, leading to the production of ammonia. However, in the nitrogen-fixing symbiosis between legumes and rhizobia, atmospheric nitrogen (N2) is directly reduced to ammonia by the bacterial nitrogenase, which questions the role of NR in symbiosis. Next to that, NR is the best-characterised source of nitric oxide (NO) in plants and NO is known to be produced during the symbiosis. In the present study, we first surveyed the three NR genes (MtNR1, MtNR2 and MtNR3) present in the Medicago truncatula genome, and addressed their expression, activity and potential involvement in NO production during the symbiosis between M. truncatula and Sinorhizobium meliloti. Our results show that MtNR1 and MtNR2 gene expression and activity are correlated with NO production throughout the symbiotic process, and that MtNR1 is particularly involved in NO production in mature nodules. Moreover, NRs are involved together with the mitochondrial electron transfer chain in NO production throughout the symbiotic process and energy regeneration in N2-fixing nodules. Using an in vivo NMR spectrometric approach, we show that, in mature nodules, NRs participate also in the regulation of energy state, cytosolic pH, carbon and nitrogen metabolism under both normoxia and hypoxia. These data point to the importance of NR activity for the N2-fixing symbiosis and provide a first explanation of its role in this process.